Cloning and expression of a β-glucosidase gene from Acremonium cellulolyticus in Saccharomyces cerevisiae - Nel, De Wet Andries (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.